Navigating sustainability through institutional change: consolidating and expanding the debate - Chikwana, Josephine; Alinaghian, Leila; Razmdoost, Kamran (European Academy of Management (EURAM), 2024)
Sustainability has become a crucial topic of discussion in both academia and practice. One perspective for understanding sustainability is through the lens of institutional change, which emphasises the need to transform norms, values, and practices to fully embrace sustainability. This review article contributes to the ongoing scholarly discourse by synthesising current literature at the intersection of institutional change and sustainability. Utilising a systematic approach, a total of 108 articles were analysed. The review provides a comprehensive understanding of the discourse and categorises existing knowledge into four key themes: triggers for change, change agents, methods for change, and resulting outcomes. This reveals the multifaceted nature of sustainability attainment through institutional change. Additionally, the review introduces four distinct institutional change models that explore change by considering the interaction between existing institutions and new sustainable institutions during the change process. This highlights the role of the existing institutional framework and the complexity of achieving sustainability. Finally, the review identifies research gaps and suggests future directions for further research in this field.
Keywords: Institutional change; Sustainability; Systematic literature review; Institutional change models